Spectrum of thyroid dysfunctions among hospitalized patients with non-critically ill coronavirus disease 2019: A cross-sectional study - Sultana, Nusrat; Banu, Hurjahan; Morshed, Md Shahed; Akter, Touhida; Saleh, Ahmed Abu; Hasanat, Muhammad Abul; Arafat, Shohael Mahmud (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Patients with coronavirus disease 2019 (COVID-19) particularly critically ill ones may present with different types of thyroid abnormalities. However, data regarding thyroid function tests (TFTs) among noncritical patients with COVID-19 are scarce. This study aimed to assess thyroid functions and their associations with the severity of illness among non-critically ill hospitalized patients with COVID-19. Methods: This cross-sectional study assessed TFTs in 87 (aged 18-65 years) RT-PCR-confirmed COVID-19 patients admitted to a tertiary-care hospital in Bangladesh. Diagnosis of non–critical illness and severity (mild, moderate, and severe) were defined by WHO’s interim guidance. Patients having known thyroid dysfunctions or taking drugs that may affect thyroid functions were excluded from the study. Serum TSH, FT4, and FT3 were measured by chemiluminescent immunoassay. Results: Majority of the patients (72%) had normal thyroid function. Among the abnormalities, the highest frequency was isolated hyperthyroxinemia (12.6%) and the rest were subclinical hypothyroidism (6.9%), subclinical thyrotoxicosis (4.6%), thyrotoxicosis (2.3%), isolated tri-iodothyroninemia (1.1%), and hypothyroidism (1.1%). Serum TSH, FT4, and FT3 levels were similar across the spectrum of noncritical illness. No significant correlation was found between the inflammatory markers (C-reactive protein, ferritin, and D-dimer) and TSH levels. Conclusions: More than one-fourth of non-critically ill hospitalized patients with COVID-19 presented with a spectrum of thyroid abnormalities with isolated hyperthyroxinemia being the most common. However, TFTs had no significant associations with the severity of illness among noncritically ill patients with COVID-19.